Sustainable Urban Regeneration with a Physical Infill Development Approach: a Case Study on Isfahan Central Region - Momeni, Farzad; Keyhanfar, Mehrdad (Journal of History Culture and Art Research, 2017)
The idea of regeneration and revitalization of historical distressed urban areas has been the focus of academic and scientific discussions over the last five decades. The evolution of these ideas, from a mere physical approach after the reconstruction of World War II ruins to the ideas of urban sustainability, has always been in line with adjustments to circumstances and accelerated developments in cities. The present study aims to investigate one of the new approaches to renewal, improvement and modernization of distressed urban areas to examine sustainable urban regeneration approach based on physical approaches. Multiple topics were examined in the case study conducted in Isfahan districts 1 and 3 to propose restructuring strategies for these historic districts using analytical methods. We employed analytical methods such as ArcGis software for reaching conclusions and obtaining results. The findings from the case study suggested a structural gap between the northwest district and Isfahan districts 1 and 3 restructuring strategies. Also, the strategies and suggestions regarding the discussion points are extracted.